RAG1 co‐expression signature identifies ETV6‐RUNX1‐like B‐cell precursor acute lymphoblastic leukemia in children. (13th May 2021) - Chen, Dongfeng; Camponeschi, Alessandro; Nordlund, Jessica; Marincevic‐Zuniga, Yanara; Abrahamsson, Jonas; Lönnerholm, Gudmar; Fogelstrand, Linda; Mårtensson, Inga‐Lill
Abstract: B‐cell precursor acute lymphoblastic leukemia (BCP‐ALL) can be classified into subtypes according to the genetic aberrations they display. For instance, the translocation t(12;21)(p13;q22), representing the ETV6 ‐ RUNX1 fusion gene (ER), is present in a quarter of BCP‐ALL cases. However, around 10% of the cases lack classifying chromosomal abnormalities (B‐other). In pediatric ER BCP‐ALL, rearrangement mediated by RAG (recombination‐activating genes) has been proposed as the predominant driver of oncogenic rearrangement. Herein we analyzed almost 1600 pediatric BCP‐ALL samples to determine which subtypes express RAG . We demonstrate that RAG1 mRNA levels are especially high in the ETV6‐RUNX1 (ER) subtype and in a subset of B‐other samples. We also define 31 genes that are co‐expressed with RAG1 ( RAG1 ‐signature) in the ER subtype, a signature that also identifies this subset of B‐other samples. Moreover, this subset also shares leukemia and pro‐B gene expression signatures as well as high levels of the ETV6 target genes ( BIRC7, WBP1L, CLIC5, ANGPTL2 ) with the ER subtype, indicating that these B‐other cases are the recently identified ER‐like subtype. We validated our results in a cohort where ER‐like has been defined, which confirmed expression of the RAG1 ‐signature in this recently described subtype. Taken together, our results demonstrate that the RAG1 ‐signature identifies the ER‐like subtype. As there are no definitive genetic markers to identify this novel subtype, the RAG1 ‐signature represents a means to screen for this leukemia in children. Abstract : The recombination‐activating genes (RAG) may play a role in leukemogenesis. We determined, therefore, in around 1600 BCP‐ALL samples which subtypes express RAG and defined a set of co‐expressed genes, the RAG1‐signature, which was thereafter used to identify potential new subtypes. We demonstrate that the RAG1‐signature identifies the recently described ETV6‐RUNX1‐like BCP‐ALL.